Some necessary conditions for convergence of the GBDF methods - Suleiman, Mohamed (American Mathematical Society, 1993)
The Generalized Backward Differentiation methods for solving stiff higher-order ordinary differential equations are described. The convergence, zero stability and consistency of these methods are defined. Next, the zero stability and consistency conditions necessary for convergence are proven. The order for which the methods are zero stable is also determined.